Pengaruh Model PBL (Problem Based Learning) terhadap Pemahaman Konsep dan Kesadaran Diri Siswa pada Pencemaran Lingkungan - El Indahnia Kamariyah; Agus Budiyono (Department of Physics Education, Universitas Mataram, 2020)
The aim of this research was to determine the effect of the PBL model on studentsÃ¢â¬â¢ conceptual understanding and self-awareness on environmental pollution. This research was an experimental research in the form of one group pretest posttest design. Through the PBL model, besides being able to increase studentsÃ¢â¬â¢ conceptual understanding, it can also increase self-awareness to protect the environment from pollution. Self-competence improvement in the form on cognitive, psychomotor and affective can be fulfilled. This research was conducted on MTS students in Pamekasan. The data analysis technique was carried out using the MANOVA test with the SPSS 16.0 program after homogeneity and normality tests were carried out. The result showed that the significance value was smaller than the specified alpha, 0.05. it shows that the PBL model has a positive and significant effect on studentsÃ¢â¬â¢ conceptual understanding and self-awareness.